The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.17796/1053-4628-39.4.315
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Evaluation of Restorative Materials in Primary Teeth Class II Lesions

Abstract: While the functional failure was the most important factor in restorative material failure, RMGIC was the most successful material in terms of biological evaluation criterion and GCR had the longest survival rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
63
2
7

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(75 citation statements)
references
References 30 publications
3
63
2
7
Order By: Relevance
“…After screening of titles and abstracts, 9 articles were suggested for full text reading (12)(13)(14)(15)(16)(17)(18)(19)(20). Based on full texts reading, 4 articles (12-15) were excluded with reasons (Table 1).…”
Section: Results:-mentioning
confidence: 99%
See 4 more Smart Citations
“…After screening of titles and abstracts, 9 articles were suggested for full text reading (12)(13)(14)(15)(16)(17)(18)(19)(20). Based on full texts reading, 4 articles (12-15) were excluded with reasons (Table 1).…”
Section: Results:-mentioning
confidence: 99%
“…no additional articles were revealed as a result of hand searching of the reference lists. Consequently, 5 studies were identified eligible for inclusion in this systematic review (16)(17)(18)(19)(20). Of the 5 articles, 2 of which (17,18) described the same trial with different follow-up time.…”
Section: Results:-mentioning
confidence: 99%
See 3 more Smart Citations